"All different, all exactly alike": identity, geopolitics, and narrative foreclosure in Voyage in the Dark and Good Morning, Midnight. Issue 1 (2nd January 2023) - Fox, Meghan C.
ABSTRACT: This essay interrogates Jean Rhys's geographically displaced, white Creole protagonists and their attempts at self-definition by examining narrative foreclosure and depictions of spatiality in Voyage in the Dark (1934) and Good Morning, Midnight (1939). By redeploying the rhetoric of European imperialism, often through the lens of mapping, Rhys shows how colonial subjects have been constrained by the imposition of colonial narratives and designations that cast them as "others." The accounts of physical spaces and the language of peers and strangers reflect an imperialist, geopolitical ideology that inflicts psychological and material harm upon Rhys's marginalized characters. Rhys exposes the flawed logic of geopolitical rhetoric that spatially and psychologically confine and define her characters; in so doing, Rhys takes away some of its power and shows that much of this colonialist rhetoric is founded upon misrecognition and the conflation of different geographic regions.